Evolution from a single relaxation process to two-step relaxation processes of Dy2 single-molecule magnets via the modulations of the terminal solvent ligands. Issue 1 (9th December 2020) - Li, Dawei; Ding, Man-Man; Huang, Yuan; Tello Yepes, David Felipe; Li, Haiyan; Li, Yahong; Zhang, Yi-Quan; Yao, Jinlei
Abstract : Three Dy2 SMMs were synthesized and characterized. The target of evolution from a single relaxation process to two-step relaxation processes was achieved by adjusting the sizes of the terminal solvent ligands. Abstract : To explore the influences of magnetic interactions on the relaxation dynamics of single-molecule magnets (SMMs) and to understand the relationship between single-ion relaxation and the relaxation of a molecular entity, it is very important to design dinuclear lanthanide-based SMMs with two-step relaxation processes. Here, three Dy2 complexes of compositions [Dy2 (L)2 (NO3 )2 (MeOH)2 ] (1 ), [Dy2 (L)2 (NO3 )2 (EtOH)2 ] (2 ), and [Dy2 (L)2 (NO3 )2 (DMF)2 ]·0.5EtOH (3 ) (H2 L = 2-(((2-hydroxy-3-methoxybenzyl)imino)methyl)-4-methoxyphenol) were successfully synthesized via elaborately introducing different terminal solvent ligands. X-ray single-crystal diffraction analyses revealed that complexes 1–3 are isostructural. The two Dy III ions of 1 and 2 both adopt D 2d symmetry, while the two Dy III centres of 3 display D 2d and D 4d symmetries, respectively. The magnetic property studies of 1–3 indicated that all three complexes exhibit single-molecule magnet (SMM) behaviours with energy barriers of 104 K for 1, 98.94 K for 2, and 76.28 K and 45.54 K for 3 under zero dc field. The target of assembling Dy2 SMMs with two-step relaxation processes was achieved by gradually increasing the sizes of the terminal solvent ligands. Complex 3 exhibits two-step relaxation processes. Complete active space self-consistent field (CASSCF) calculations were performed on 1–3 to rationalize the observed differences in the magnetic behaviour. It is found that both the angles θ between the magnetic axis and the vector connecting two Dy III ions and the symmetries of Dy III ions are vital factors that affect the energy barriers of 1–3 . The high local symmetries of the central metals in 1 and 2 make the complexes act as SMMs with higher energy barriers, while the smaller θ angle and different symmetries of the two Dy III ions render complex 3 as a SMM with a two-step relaxation process. This work demonstrates a new methodology for preparing SMMs with two-step relaxation processes by fine-tuning the terminal solvent ligands.